Perilaku Tes HIV pada Laki-Laki yang Berhubungan Seks dengan Laki-Laki (LSL) di Provinsi Bali - Putu Krisna Saputra; Bagoes Widjanarko (Jurnal Promosi Kesehatan Indonesia, 2016)
ABSTRACTMen who have sex with men (MSM) is a high risk population in infected with HIV and AIDS and Sexually Transmitted Infections (STIs) . Based on data from the Integrated Biological and Behavioral Surveillance (IBBS) in 2011 found that HIV prevalence among MSM is between 2.4 % to 17 % . Based on data from the Gaya Dewata Foundation , the number of new MSM reached in 2013 amounted to 1,322 people . However , the number of HIV tests among MSM in 2013 only amounted to 874. While the number of new HIV cases among MSM in 2013 amounted to 118 cases , this number increased by two times in 2011, which is amounted to 50 cases. This research is a quantitative study with cross sectional approach. The number of respondents 110 people choosen by purposive sampling technique.Quantitative data collection techniques through interviews with the questionnaire. Data were analyzed using univariate analysis with frequency distribution, using the chi-square bivariate, and multivariate logistic regression. The results showed that the variables associated with HIV testing behavior among MSM in Bali Province is the type of place to stay and history of STIs . Multivariate analysis showed that a history of STIs ( p value = 0.005 ) is the variable that has the most significant effect on the behavior of HIV testing in MSM in Bali Province with OR of 3.400. HIV testing in MSM behavior quite well. The majority of respondents had an HIV test within 0-6 months ago. Most respondents did last HIV test in Denpasar. Forms of HIV tests performed by the respondent is entirely voluntary counseling and testing ( VCT ) as well as all respondents knew of his HIV test results.Keywords: MSM, HIV Testing, Bali